Temporal variation of tropospheric NO2 columns in Vietnam during 2015–2020 - Nguyen Ha Trang; Nguyen Thi Tuyet Nam (Journal of Technical Education Science, 2021)
Nitrogen dioxide (NO2) in the atmosphere can be measured using the tropospheric NO2 columns, indicating the number of molecules of NO2 in an atmospheric column from the ground surface to the top of the atmosphere above a square centimeter of the surface. In this study, the temporal variations of tropospheric NO2 columns in Vietnam during 2015–2020 were investigated. To do this, data on the columnar NO2 obtained from the Ozone monitoring instrument (OMI) onboard the NASA’s Earth orbiting satellite Aura were used. Consequently, northeastern Vietnam showed the highest values of the tropospheric NO2 columns over the whole study period (2015–2020), suggesting that this area would be a hot spot of NO2 pollution in Vietnam. In addition, the lowest and highest mean levels of columnar NO2 were found in 2020 and 2016, respectively. However, there is no statistical significance among the columnar NO2 in 2015–2020. Regarding the monthly variation, March and April exhibited the highest levels of tropospheric NO2 columns, which would be affected by frequent combustion activities (e.g., post-harvesting combustion) and meteorological conditions, such as lower air temperature. Results of this study can contribute to an understanding of NO2 pollution in Vietnam over long period.